Keunggulan pati kulit singkong (Manihot esculenta) sebagai bahan pembuatan edible film ramah lingkungan - Fauziyah, Lathifah Zahra; Suhara, Nur Fajriyah; Yunita, Shella; Priyandoko, Didik; Surtikanti, Hertien Koosbandiah (Applied Environmental Science, 2024)
The use of plastic packaging is difficult to decompose by microbes, this raises the idea of making edible films in food packaging. Cassava peel starch can be the main component material in making this edible film, because its content can be used as an edible film making material and can reduce cassava peel waste. The aim is to understand and recognize the effectiveness of making edible film from cassava peel starch because the utilization of cassava peel as agroindustrial waste of cassava processing can be useful to reduce the amount of cassava peel waste and the use of plastic. The research method used is the literature study method. Cassava peel is the most effective material for making edible film.  Researchers should conduct further research related to the use of natural materials that can make edible films more durable than before.